2018
DOI: 10.1080/20002297.2018.1495976
|View full text |Cite
|
Sign up to set email alerts
|

Functional profiles of coronal and dentin caries in children

Abstract: Background: Dental caries results from a dysbiosis of tooth-associated biofilms and frequently extends through enamel into dentin which has a different structure and composition.Objective: To evaluate the metatranscriptome of caries to determine the metabolic potential of caries communities compared with health.Design: Samples from children, caries-free (CF: n = 4) or with coronal (CC: n = 5) or dentin (DC: n = 5) caries were examined for gene expression potential. Functional profiling was performed using HUMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 44 publications
1
40
1
Order By: Relevance
“…Our previous study tracked the changes of microbiota over time from the healthy status to caries occurrence and caries progression, thus developed a model for caries prediction and suggested a panel of Prevotella species that may be closely related to caries disease 21,22 . Prevotella's association with caries was also verified by many other studies 24,25 . These indicated that the overexpressed collagenases for proteolytic metabolism in Prevotella species may lead to the progression of dental caries 23 .…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Our previous study tracked the changes of microbiota over time from the healthy status to caries occurrence and caries progression, thus developed a model for caries prediction and suggested a panel of Prevotella species that may be closely related to caries disease 21,22 . Prevotella's association with caries was also verified by many other studies 24,25 . These indicated that the overexpressed collagenases for proteolytic metabolism in Prevotella species may lead to the progression of dental caries 23 .…”
Section: Discussionsupporting
confidence: 65%
“…A number of studies have also reported strong association between several Prevotella spp. (in particular P. denticola) and caries status as well [23][24][25] .…”
mentioning
confidence: 99%
“…For instance, similar levels of relative abundance in samples from caries‐free and coronal caries‐active children were revealed for the genera Neisseria , Veillonella , Granulicatella , Gemella , as well as the species Veillonella parvula , S . sanguinis , Streptococcus cristatus (Kressirer et al, ). Recognition of the oral core microbiome would be useful for a deeper understanding of the caries pathogenesis and providing insight into microbial interactions in polymicrobial diseases (Shiba et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Caries is developed when pH decreases due to the fermentation by acid‐producing bacteria of readily available carbohydrates to organic acids, which consequently leads to overgrowth of acidotolerant bacteria and suppression of acid‐sensitive species (Bowen, ; McLean et al, ; Zero et al, ). Metatranscriptome analysis of the caries has confirmed “ecologic plaque hypothesis”; genes with increased expression have been found to contribute the metabolic changes favourable for development of acidogenic and acid‐tolerant microbial communities (Kressirer et al, ).…”
Section: Introductionmentioning
confidence: 97%
“…More evidence is now emerging regarding the prevalence and epidemiology of Scardovia wiggsiae, particularly among children with early childhood caries (ECC) [7,8]. These studies clearly describe the potential for caries development and pathology among children and teenagers both in the presence and absence of other clearly defined cariogenic organisms, such as Streptococcus mutans [9][10][11].…”
Section: Introductionmentioning
confidence: 99%